Modern Pollen Monitoring Of Native Trees In Belgrad Forest, Istanbul (Northwestern Turkey) - Karhoglu, Nurgul; Caner, Hulya; Akkemik, Unal; Kose, Nesibe; Kindap, Tayfun (Aperta, 2015)
This paper presents the results of a study of pollen deposition across vegetational gradients in Belgrad Forest, from closed forest to open situations (forest, forest edge to an open area) between September 2007 and September 2009. In all three pollen traps, the annual pollen influx values of Carpinus and Quercus were dominant, and followed by Alnus and Corylus. Due to heavy rainfall during the flowering period, total pollen influx was considerably lower in the second year.